Comparison Of Waterfall And Prototyping Models In Research And Development (R&D) Methods For Android-Based Learning Application Design - Rachma, Nur; Muhlas, Itawiranda (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Design of learning applications that use Development Methods (Research and Development/R&D) using a commonly used system development methodology, namely SDLC (System Development Life Cycle). Several stages of SDLC consist of planning, analysis, design, implementation to system maintenance. The SDLC concept is the basis of various types of software development models to form a framework in planning and controlling information systems. The SDLC model that is often used in research and development (R&D) research for the development of Android -based learning applications is a waterfall and prototyping model. The comparison of the two models states that the waterfall model is more suitable for a system or software that is generic or in the form of software that can provide services to the buyer. While prototyping is more suitable for customize systems or software, meaning software made based on demand and needs (even certain situations and conditions). In accordance with the analysis obtained, the two methods have the advantages and disadvantages of each, so that the developer can choose which method is more suitable for the development of the software.